Characteristics of the varietal gene pool of soft spring wheat in the Republic of Tatarstan according to genetic markers of resistance to stripe (yellow) rust - Natalia B. Baranova; Victoria V. Kostenko; Mira L. Ponomareva (Аграрная наука Евро-Северо-Востока, 2025)
In the Republic of Tatarstan, common spring wheat (Triticum aestivum L.) occupies a leading position in crop rotations and is sown annually on more than 400,000 hectares. Diseases caused by the phytopathogen Puccinia striiformis, which can reduce yields by up to 90 %, are a particular threat to wheat crops. In our work, 25 breeding cultivars of soft spring wheat bred by the Tatar Scientific Research Institute of Agriculture were genotyping for yellow rust resistance genes – Yr1 (gwm311), Yr5 (S23M41 and S19M93), Yr10 (Xpsp3000), Yr15 (Xgwm413) and Yr17/Lr37/Sr38 (Ventriup/LN2). The presence of the Yr5-associated marker S23M41 in the genotype was detected in 56 % of the tested cultivars. The S19M93 marker was identified in 84 % of the studied cultivars. The presence of the Xgwm413 marker was detected in 32 % of the tested spring wheat varieties. Negative results were obtained for the identification of the molecular marker Ventriup/LN2 associated with genes for resistance to stripe, leaf and stem rust in all the studied cultivars. The results obtained indicate the genetic diversity of these cultivars with regard to resistance to P. striiformis. The presence of three yellow rust resistance genes (Yr1, Y5 and Yr15) was detected for ‘Barakat’, ‘Yoldyz’, ‘Kazanskaya Yubileynaya’, ‘Sitara’, ‘Ekada 113’ and ‘Ekada 214’.